Effects of environmental metal and metalloid pollutants on plants and human health: exploring nano-remediation approach - Priyadarshani Rajput; Abhishek Singh; Shreni Agrawal; Karen Ghazaryan; Vishnu D. Rajput; Hasmik Movsesyan; Saglara Mandzhieva; Tatiana Minkina; Athanasios Alexiou (Stress Biology, 2024)
Abstract Metal and metalloid pollutants severely threatens environmental ecosystems and human health, necessitating effective remediation strategies. Nanoparticle (NPs)-based approaches have gained significant attention as promising solutions for efficient removing heavy metals from various environmental matrices. The present review is focused on green synthesized NPs-mediated remediation such as the implementation of iron, carbon-based nanomaterials, metal oxides, and bio-based NPs. The review also explores the mechanisms of NPs interactions with heavy metals, including adsorption, precipitation, and redox reactions. Critical factors influencing the remediation efficiency, such as NPs size, surface charge, and composition, are systematically examined. Furthermore, the environmental fate, transport, and potential risks associated with the application of NPs are critically evaluated. The review also highlights various sources of metal and metalloid pollutants and their impact on human health and translocation in plant tissues. Prospects and challenges in translating NPs-based remediation from laboratory research to real-world applications are proposed. The current work will be helpful to direct future research endeavors and promote the sustainable implementation of metal and metalloid elimination.